ANALISIS PENYELESAIAN SENGKETA AQAD MURABAHAH DALAM PUTUSAN PENGADILAN NEGERI BUKITTINGGI NOMOR 08/PDT.BTH/2004/PN.BT DAN PUTUSAN PENGADILAN AGAMA BUKITTINGGI NOMOR 284/PDT.G/2006/PA.BKT - Indra Fardi (IAIN Batusangkar, 2021)
The problem in this research is how the aqad murabahah dispute resolution process and the juridical analysis of the verdict in the Judgment of the Bukittinggi District Court No.08 / PDT.BTH / 2004 / PN.BT. The second problem is How is the aqad murabahah dispute resolution process and judicial analysis Bukittinggi Religious Court No.284 / Pdt.G / 2006 / PA.Bkt. The research findings are the dispute over the al-murabaha sale and purchase agreement of Bank Bukopin Syariah Bukittinggi which was decided by the Bukittinggi Religious Court is a dispute that has permanent legal force or inkrak van gewijsde before Act No. 3 of 2006 is effective about seizing the execution of collateral, then it is not the principle of nebis in idem. The Bukitinggi Religious Court has the authority to examine and decide the case of al-murabaha sale and purchase agreement Bank Bukopin Syariah Bukittinggi. The Bukitinggi Religious Court bases its decision on: KUH Perdata, Fatwa of the Indonesian Ulema Council and the Al-Hadith. Settlement of dispute defaults best with Court decisions. The need for a law on sharia economics in addition to the Al-Quran and Al-Hadith as a guideline for sharia economic actors. Islamic banks must implement Islamic law in a fixed manner as part of worship.